2015
DOI: 10.1016/j.jiac.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the need for carbapenems to treat community-acquired and healthcare-associated pneumonia

Abstract: Carbapenems have an overall broad antibacterial spectrum and should be protected against from the acquisition of drug resistance. The clinical advantages of carbapenem in cases of pneumonia have not been certified and the need for antipseudomonal antimicrobial agents to treat healthcare-associated pneumonia (HCAP) remains controversial. We introduced an antimicrobial stewardship program for carbapenem and tazobactam/piperacillin use and investigated the effects of this program on the clinical outcomes of 591 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…However, in a recent study, 31.66% and 10% resistance to meropenem and imipenem, respectively, were found in E. coli isolated from cloacal swab of poultry (Sobur et al., 2019 ). Carbapenem antibiotics are considered as ‘last‐line agents’ as they are used to treat infections due to MDR bacteria that are non‐responsive to other classes of antibiotics (Kamata et al., 2015 ). Generally, the emergence of carbapenem‐resistant strain could occur through the acquisition of carbapenem‐resistance genes via plasmid‐mediated horizontal gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study, 31.66% and 10% resistance to meropenem and imipenem, respectively, were found in E. coli isolated from cloacal swab of poultry (Sobur et al., 2019 ). Carbapenem antibiotics are considered as ‘last‐line agents’ as they are used to treat infections due to MDR bacteria that are non‐responsive to other classes of antibiotics (Kamata et al., 2015 ). Generally, the emergence of carbapenem‐resistant strain could occur through the acquisition of carbapenem‐resistance genes via plasmid‐mediated horizontal gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…However, even patients admitted to ICUs may have just as great 1 a risk of harm from over-coverage with these agents, including renal toxicity and secondary infection [34]. In pneumonia, anti-MRSA and antipseudomonal therapy has not been associated with improved outcomes in observational cohort studies [8,10], or pre-post analyses of antimicrobial stewardship programs [35]. For the VA population, we previously failed to establish a benefit of empiric anti-MRSA therapy, even when used in those with elevated risk for MRSA pneumonia [36].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this evidence, the 2005 ATS/IDSA guidelines for nosocomial pneumonia included recommendations for HCAP treatment, suggesting empirical coverage of MDR pathogens [3]. Since then, subsequent studies were conducted in South Korea, Japan, and Spain, but most studies showed that S. pneumoniae is the most common causative agent of HCAP, similar to CAP (Table 3) [567894445464954556162636465]. In addition, although the proportion of MDR pathogens is higher in HCAP, some studies revealed indistinguishable etiologic distribution of causative agents between HCAP and CAP [56789].…”
Section: Comparison Of Etiologic Distribution Between Community-acquimentioning
confidence: 99%
“…In comparison, the disease burden of pneumococcal pneumonia might be persistent among at-risk HCAP populations particularly residing in LTCF with missed opportunity of vaccination [70], as pneumococcal pneumonia outbreaks have been reported among unvaccinated nursing home residents [7172]. In some studies conducted in Japan, the proportion of pneumococcal pneumonia in HCAP was similar or rather higher compared to that of CAP (Table 3) [689]. The concerning point is that MDR S. pneumoniae might be transmitted among LTCF residents with repeated antibiotic exposure.…”
Section: Comparison Of Etiologic Distribution Between Community-acquimentioning
confidence: 99%
See 1 more Smart Citation